Enzymatic synthesis of deoxyribo-oligonucleotides of defined sequence. Deoxyribo-oligonucleotide synthesis* - Gillam, Shirley (1974)
An enzyme, which is probably identical with polynucleotide phosphorylase, was prepared from Escherichiacoli B. In the presence of Mn(2+) it catalyzes the addition of one (and to a slight extent more) residue of deoxyribonucleotide residue from the diphosphate to an oligodeoxyribonucleotide primer. The shortest effective primers contained three phosphate residues. Ribodinucleotides were effective as primers and accepted two or three deoxyribonucleotide residues under these conditions. The application of the procedures to the convenient synthesis of certain defined oligodeoxyribonucleotides up to nine residues long is discussed.